(untitled) (Biocenosis, 2025)
The northern region of Cartago is characterized by its fertile land and abundant water resources, which benefit the local economy. In this context, a qualitative study was conducted using the participatory action research (PAR) methodology, with the objective of strengthening community-based management for water sustainability through a non-formal environmental education program. This initiative was carried out in collaboration with the staff from the Irazú Volcano National Park, the Commission for the Management of the Birrís and Paez Rivers (COBIRRIS-PAEZ), and the Associations for the Administration of Communal Aqueduct and Sewage Systems (ASADAS). In the first phase, data was collected through in-depth interviews, focus groups, participant observation, and field visits with ASADAS personnel, environmental education staff from the Irazú Volcano National Park (PNVI), and members of the Commission. In the second phase, a questionnaire was applied to guide the actions and collaboratively design the non-formal environmental education program. Notable outcomes included proposals and ideas from the local population for activities related to good environmental practices.